Monoclonal antibodies constructed from COVID-19 convalescent memory B cells exhibit potent binding activity to MERS-CoV spike S2 subunit and other human coronaviruses - Peng, Yuan; Liu, Yongcheng; Hu, Yabin; Chang, Fangfang; Wu, Qian; Yang, Jing; Chen, Jun; Teng, Shishan; Zhang, Jian; He, Rongzhang; Wei, Youchuan; Bostina, Mihnea; et al. (Frontiers in Immunology, 2022)
The Middle East respiratory syndrome coronavirus (MERS-CoV) and the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) are two highly contagious coronaviruses causing MERS and COVID-19, respectively, without an effective antiviral drug and a long-lasting vaccine. Approaches for diagnosis, therapeutics, prevention, etc. are urgently needed, particularly for SARS-CoV-2 that are continuedly spreading and evolving. Our previous study discovered that >60% of sera from COVID-19 convalescents, but only a small proportion (<8%) from general population, showed binding activity with MERS-CoV spike protein, thus indicating that SARS-CoV-2 infection boosted the production of antibodies cross-reactive with MERS-CoV. To generate antibodies specific to both SARS-CoV-2 and MERS-CoV, we initially screened 60 sera from COVID-19 convalescents against MERS-CoV spike extracellular domain and subunits S1 and S2. Thirty-four sera showed binding activity with MERS-CoV S2, and its endpoint titers positively correlated with that of SARS-CoV-2 S2 antibodies. By sorting memory B cells from COVID-19 convalescents, we constructed 38 monoclonal antibodies (mAbs), of which 11 showed binding activity with MERS-CoV S2. Moreover, 9 of these 11 mAbs showed potent cross-reactivity with spike proteins of alphacoronaviruses (229E and NL63) and betacoronaviruses (SARS-CoV-1, SARS-CoV-2, OC43, and HKU1). Five mAbs also showed weak neutralization effect against MERS-CoV spike pseudovirus. Epitope analysis revealed that 3 and 8 mAbs bound to linear and conformational epitopes in MERS-CoV S2, respectively. In summary, we have constructed a panel of antibodies with broad-spectrum reactivity against all seven human coronaviruses, thus facilitating the development of diagnosis methods and vaccine design for multiple coronaviruses.